Anticancer Activity of Novel Gabexate Mesilate Mimetics in Colorectal Cancer Cells. Issue 24 (26th June 2018) - Khan, Amber; Wani, Mohmmad Younus; Al‐Bogami, Abdullah Saad; Subramanian, Kumar; Kandhavelu, Jeyalakshmi; Ruff, Paul; Penny, Clement
Abstract: Despite there being significant advances in colorectal cancer (CRC) treatments, recurrence and chemoresistance remain a challenge in the treatment of patients. During the process of autophagy, cancer cells acquire anoikis resistance and escape chemotherapy. High Mobility Group Box 1 (HMGB1) protein is a key mediator of autophagy and can be exploited to develop effective targeted anticancer therapies. Gabexate mesilate (GM) used in the treatment of pancreatitis is both a synthetic inhibitor of HMGB1 and of metastasis. Structural analogues of GM hold promise to suppress HMGB1 functionality to arrest cancer growth, recurrence and resistance mechanisms. We synthesized structural GM mimetics (GMMs) and evaluated their anticancer activity. Considering the critical role of HMGB1 in the cell cycle, we analyzed cell cycle response to active GMMs in CRC cells in a Muse flow cell analyzer. Docking studies were further performed to predict the binding modes and affinity of active GMM for HMGB1. A total of thirteen GMMs were synthesized and their anticancer activity was evaluated on each of the SW480, HT29 and DLD1 CRC cell lines. Of the 13‐novel synthetic GMMs assessed, A1, A2, A3 andA6 were found to be the most active, with anticancer inhibitory concentrations (IC80) of 250–500μg/mL. Treatment with active GMM′s resulted in CRC cells being arrested mainly in preparatory phases of the cell cycle. Docking studies established that the active GMMs possessed specific binding affinity with the target, compared to the inactive GMM. Abstract : In this study, we synthesized thirteen novel structural analogues of gabexate mesilate and tested them against colorectal cancer cells for their growth and cell cycle response. Mimetics A1, A2, A3 and A6 were found most active against HT29, SW480 and DLD1 colorectal adenocarcinoma cells. Molecular docking studies established A1, A2 and A6 mimetics to interact with DNA in high mobility group box 1 (HMGB1)‐DNA complex. Mimetics A1‐A3 and A6 arrested HT29 and DLD1 cells in their preparatory phases‐ G0/G1 and G2/M, indicating a HMGB1 mediated cell cycle response.